Swallow root (Decalepis hamiltonii) pectic oligosaccharide (SRO1) induces cancer cell death via modulation of galectin-3 and survivin. (15th April 2018) - Mallikarjuna, S.E.; Dharmesh, Shylaja M.
Highlights: SRO1 from Swallow Root is an arabinogalactan rhamnogalacturonan I. SRO1 possessed anticancer activity via the blockade of galectin-3 and survivin. SRO1 thus may find application as an effective anticancer therapeutics. Abstract: Swallow root pectic oligosaccharide fraction (SRO1) from swallow root pectic polysaccharide (SRPP) possessed a molecular size of 831 Da. Structural analysis revealed that it is a rhamnogalacturonan I type, bearing arabinogalactan side chain with β-d -(1→4) galactose along with α-l -Araf (1→5)-α-l -Araf (1→3) structure on α-d -GalA- O Ac-(1→2)-α-l - R ha-(1→4)- linear backbone. β-d (1→4) linked galactose being the specific sugar for galectin-3, SRO1 had potentials in inhibiting galectin-3 mediated cancer progression. SRO1 inhibited galectin-3 mediated agglutination, in vitro, effectively with MIC of 1.08 μg/ mL and down regulated mRNA levels of galectin-3 (∼92%) along with its downstream key protein that inhibits apoptosis – survivin (∼78%) suggesting the capability of SRO1 in inhibiting galectin-3 mediated cancer promoting pathway. This is the first report, which highlights the inhibition of interplay of galectin-3 and survivin by a dietary pectic oligosaccharide.